Conducting spirometry in occupational health at COVID-19 times: international standards - Ranzieri, Silvia; Corradi, Massimo (La Medicina del Lavoro, 2021)
Spirometry is a commonly performed assessment of lung function for diagnostic purposes as well as for monitoring of chronic lung diseases. The last international standardization of this technique was published in 2005. After 14 years, a group of experts from two leading scientific societies, American Thoracic Society (ATS) and European Respiratory Society (ERS), published a joint position that updated the standardization of spirometry, with an extensive criteria re-organization, including key updates such as: relative contraindications, instrumentation requirement to meet the International Organization for Standardization (ISO) standards, quality assurance, operator training, pre-test requirements, acceptability and usability criteria. New standards underline three key elements to obtain high quality pulmonary function data: an accurate and precise instrumentation, a patient/subject capable of performing acceptable and repeatable measurements, and a motivated technologist to elicit maximum performance from the patient. Never- theless, although COVID-19 pandemic has enormously impacted and limited a widespread application of spirometry, it has prompted much attention on hygienic procedures and on further research on noncontact spirometers.